Metamaterial‐based antennas for integration in UWB transceivers and portable microwave handsets. Issue 1 (16th September 2015) - Alibakhshi‐Kenari, Mohammad; Naser‐Moghadasi, Mohammad; Ali Sadeghzadeh, Ramazan; Singh Virdee, Bal
ABSTRACT: Two planar antennas based on metamaterial unit‐cells are designed, fabricated, and tested. The unit‐cell configuration consists of H‐shaped or T‐shaped slits and a grounded spiral. The slits essentially behave as series left‐handed capacitance and the spiral as a shunt left‐handed inductance. The unit‐cell was modeled and optimized using commercial 3D full‐wave electromagnetic simulation tools. Both antennas employ two unit‐cells, which are constructed on the Rogers RO4003 substrate with thickness of 0.8 mm and εr = 3.38. The size of H‐shaped and T‐shaped unit cell antennas are 0.06λ0 × 0.02λ0 × 0.003λ0 and 0.05λ0 × 0.02λ0 × 0.002λ0, respectively, where λ0 is the free–space wavelength. The measurements confirm the H–shaped and T–shaped unit‐cell antennas operate across 1.2–6.7 GHz and 1.1–6.85 GHz, respectively, for voltage standing wave ratio (VSWR) < 2, which correspond to fractional bandwidth of ∼140% and ∼ 145%, respectively. The H‐shaped unit‐cell antenna has gain and efficiency of 2–6.8 dBi and 50–86%, respectively, over its operational range. The T‐shaped unit‐cell antenna exhibits gain and efficiency of 2–7.1 dBi and 48–91%, respectively. The proposed antennas have specifications applicable for integration in UWB wireless communication systems and microwave portable devices. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:88–96, 2016.